Performance challenges in a newly established clean room at Omid Hospital, Isfahan, Iran: A descriptive study - Mehrnaz Vaez; Mehran Sharifi; Sahar Karimi; Azadeh Moghaddas (Wolters Kluwer Medknow Publications, 2023)
Objective: This study aimed to comprehensively assess the challenges faced by a newly established clean room in the oncology center of Omid Hospital, Isfahan, Iran, one of the first of its kind in the country. The research also sought to identify the underlying causes of these challenges and propose potential solutions to address them. Methods: A 6-month cross-sectional study was conducted from December 2021 to May 2022. International guidelines such as British Columbia Cancer Agencies' guideline of hazardous drugs, the National Institute for Occupational Safety and Health guideline for working with hazardous drugs, and United States pharmacopeia related to cleanroom performance were studied, translated, and summarized into a checklist. The staff performance in Omid Hospital's clean room was compared to the data collection form, and all medication errors were documented and analyzed. The study also explained the underlying causes of these challenges and proposed potential solutions. Findings: Among 1005 chemotherapy regimens, 836 errors were detected, stemming from issues such as engineering and construction challenges, lack of human resources and essential equipment, and budgetary constraints. Conclusion: Despite the involvement of a trained oncology clinical pharmacist, Omid Hospital's cleanroom faces significant challenges within the medical and hospital system, leading to non-standard challenges. The study recommends multidisciplinary approaches in the hospital to mitigate these challenges and improve cleanroom performance.